Pengaruh Fly Ash Terhadap Densitas Dan Kuat Tekan Bata Ringan - Hilman Maulana, Dikky; Ary Wahyudie, Ilham; Erwansyah, Erwansyah (Jurnal Inovasi Teknologi Terapan, 2023)
Utilization of fly ash (fly ash) as an additive in the formation of lightweight bricks has a positive impact from an environmental point of view. Fly ash is a very fine residue from burning coal. The fineness of fly ash grains can potentially cause air pollution. Handling of fly ash (fly ash) at this time is still limited to stockpiling on vacant land. The addition of fly ash to the lightweight brick mixture can be a good mineral additive for lightweight bricks because the fly ash contains silica, which is binding. In this study, we will identify the benefits of fly ash (fly ash) as a partial replacement material for the use of cement in lightweight bricks. The purpose of this study was to determine the effect of adding fly ash as a partial replacement for cement on the density and compressive strength of lightweight bricks. Variations in the percentage of fly ash used are 15%, 25%, and 35%. This study used six beam-shaped test samples, with each sample being replicated three times with a mold size of 100 mm x 50 mm x 50 mm. From this study, it was found that the best density value was when using 25% fly ash, which was 1482.4 kg/m3 with the highest compressive strength value of 17.7 MPa. It can be concluded that the percentage of fly ash used affects the density of lightweight bricks. The use of 25% fly ash on lightweight bricks produces lightweight bricks with maximum compressive strength.